Lessons of an Exhibition: Opening of the ‘Mosaics from the Past and the Present of Higher Education in Pécs’ Exhibition - Vonyó, József (Per Aspera ad Astra, 2017)
Photo: University of Pécs, Historical Collection Department of the Central Library